Analisis Penerapan Prinsip Akuntabilitas dan Transparansi Tethadap Pengelolaan Keuangan Desa (Studi Kasus Pada Desa Sidumulyo, Distrik Oransbari) - Syarifuddin, Syarifuddin; Asidik, Kania Ekgy; Wuriasih, Anik Ekgy (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2024)
This study analyzes the implementation of the principles of accountability and transparency in the planning, administration and budgeting of Sidomulyo Village funds, Oransbari District, to understand the implementation of the principles of accountability and transparency and identify the obstacles that arise. This study uses a qualitative approach, data is collected through observation, interviews, and documentation. The results of the study indicate that the implementation of the principle of accountability has been applied in Sidomulyo Village, carried out through the preparation of honest and open accountability reports. The principle of transparency has been applied in Sidomulyo Village by providing budget information through billboards and information boards. However, there are several obstacles such as low community participation and lack of adequate electronics. This study recommends that village officials increase community participation through education such as socialization carried out during village meetings or events